2008
DOI: 10.1002/ajmg.a.32190
|View full text |Cite
|
Sign up to set email alerts
|

3q29 interstitial microduplication: A new syndrome in a three‐generation family

Abstract: Microdeletion and microduplication genetic syndromes are known to be a significant cause of developmental delay and dysmorphology. Utilizing high-resolution chromosome analysis, array CGH and SNP technologies we identified a novel genomic syndrome comprising of an interstitial duplication of approximately 1.61 Mb at the distal end of chromosome 3 band q29. The imbalance was present in five individuals in a three generation family with clinical features including mild to moderate mental retardation and microcep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 19 publications
9
63
0
Order By: Relevance
“…However, 3q29 microduplications have been reported in asymptomatic parents of individuals with mild-tomoderate mental retardation and, therefore, its clinical significance is unclear. 20,21 Additionally, the seizures present in our case have not been reported in other patients with 3q29 microduplications. 20,21 FOXG1 has been shown to have an important role in the developing brain.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…However, 3q29 microduplications have been reported in asymptomatic parents of individuals with mild-tomoderate mental retardation and, therefore, its clinical significance is unclear. 20,21 Additionally, the seizures present in our case have not been reported in other patients with 3q29 microduplications. 20,21 FOXG1 has been shown to have an important role in the developing brain.…”
Section: Discussionsupporting
confidence: 44%
“…20,21 Additionally, the seizures present in our case have not been reported in other patients with 3q29 microduplications. 20,21 FOXG1 has been shown to have an important role in the developing brain. 22 It encodes a transcriptional repressor protein exclusively expressed in the fetal and adult brains.…”
Section: Discussionsupporting
confidence: 44%
“…. The approximate location of the duplication described previously is shown (Lisi et al, 2008). The region of recurrent 3q29 microdeletion described in Willatt et al (2005) is also indicated (white bar); this corresponds to the duplication reported in Ballif et al (2008).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that this region is susceptible to nonallelic homologous recombination, which could result in reciprocal exchange events at chromosome 3q29. Two recent reports describe the apparent reciprocal microduplication event: the first, in the heterozygous state in five individuals of a three-generation pedigree (Lisi et al ., 2008), and the second including 19 cases, five of which appear to be the reciprocal event with the remainder overlapping this region (Ballif et al ., 2008). Here, we describe index cases from four pedigrees (Case 1 apparently de novo, Case 2 a mother-child inheritance, Case 3 a nuclear family with multiple members carrying the duplication, and Case 4 an adopted child from whom information about the biological parents is unavailable).…”
mentioning
confidence: 99%
“…Mutational analysis of the genes located in the deletion region leads the identification of the causal gene(s) of ID, with or without congenital anomalies. Duplications of some chromosomal segments are reported to be associated with ID (1q21.1, BrunettiPierri et al, 2008;3q29, Goobie et al, 2008;Lisi et al, 2008;16p13.11, Hannes et al, 2009;Xq28, Van Esch et al, 2005). This indicates that increased gene dosage(s) are associated with ID.…”
Section: Partial Aneuploidy (Partial Monosomy and Partial Trisomy)mentioning
confidence: 99%